Multiple virus infections of lablab [ Lablab purpureus (L.) Sweet] in Nigeria - Odedara, O.O.; Hughes, J.; Odebode, A.C.; Odu, B.O. (Springer, 2008)
Leaf samples of Lablab purpureus collected from two agroecological zones of Nigeria—the northern guinea savanna zone (NGSZ) and the derived savanna zone (DSZ)—were infected with viruses when serologically indexed against available antisera. Approximately 31.1 and 81.1% of the leaf samples collected from the NGSZ and DSZ, respectively, were infected. Seven viruses were found: Bean common mosaic virus (BCMV), Cowpea aphid-borne mosaic virus (CABMV), Cucumber mosaic virus (CMV), Cowpea mottle virus (CPMoV), Cowpea severe mosaic virus (CPSMV), Southern bean mosaic virus (SBMV) and Tobacco mosaic virus (TMV) were detected from samples collected from NGSZ, while CMV, CPMoV, Cowpea mosaic virus (CPMV) and CPSMV were detected from samples from DSZ.